Gradient Refractive Index (GRIN) Optics: Monolithic Chalcogenide Optical Nanocomposites Enable Infrared System Innovation: Gradient Refractive Index Optics (Advanced Optical Materials 10/2020). Issue 10 (18th May 2020) - Kang, Myungkoo; Sisken, Laura; Lonergan, Charmayne; Buff, Andrew; Yadav, Anupama; Goncalves, Claudia; Blanco, Cesar; Wachtel, Peter; Musgraves, J. David; Pogrebnyakov, Alexej V.; Baleine, Erwan; Rivero‐Baleine, Clara; et al.
Abstract : This cover picture, referring to article number 2000150 by Myungkoo Kang, Kathleen A. Richardson and co‐workers, illustrates that multi‐component Ge–As–Pb–Se chalcogenide glasses are capable of forming transparent optical glass ceramic nanocomposites with the potential for use as infrared gradient refractive index optical components. Through a simple gradient heat treatment protocol, the glass system is converted to a nanocomposite where the spatially varying volume fraction of nucleated nanocrystals defines the resulting nanocomposite's effective optical properties. This modification results in systematic variations in refractive index and Abbe number of the transmissive nanocomposites. These data are critical in that they provide the design input data required to engineer arbitrarily‐shaped, single‐component gradient refractive index lenses with minimum spectral aberration. (Cover illustration: courtesy of Mia Truman.)